Soil organic matter in oxisols of the Brazilian cerrados - Neufeldt, Henry; Resck, DVS; Ayarza, Miguel Angel; Zech, W. (International Center for Tropical Agriculture, 1999)
Little is known about the sustainability of cultivation systems in the Brazilian savannas, also known as the Cerrados, despite its increasing significance for that country`s agriculture. To characterize management effects and follow alterations of organic compounds in different fractions, we studied whole-soil samples and particle-size separates from clayey and loamy Oxisols under crops, pastures, reforested sites, and savanna. We assessed soil organic carbon (SOC), polysaccharides, and CuO oxidation products (VSC-lignin). Few changes were found in SOC contents of topsoil (0-12 cm) under different land uses after 10-20 years. But organic carbon clearly diminished under continuous cropping on the loamy soil and under reforestation with pine on the clayey soil. Management effects on SOC were more apparent in sand fractions, suggesting that particulate organic matter (POM) was affected most. In the clay fraction, only minor effects were noted. Carbon-normalized polysaccharide contents were enriched under pastures and depleted under pine, but generally followed a similar distribution to that of SOC. Overall, both polysaccharides and VSC-lignin were closely related to soil porosity. Plant-derived polysaccharides and lignin contents were probably regulated by water availability to soil microbes, so that decomposition was usually more advanced in the clayey soils. Ten years of continuous cropping lowered litter inputs, thus reducing POM, whereas humified organic matter (OM) was unaffected. Planting eucalyptus or well-managed pastures, which produce high amounts of POM, would thus rapidly reverse soil degradation. Continuous cropping does eventually reduce the humified fraction and results in a substantial loss of soil fertility, which is only slowly reversible.